KAJIAN FORM AND STYLE TEORI BORDWELL PADA KARYA FILM PENDEK BERTEMA BUDAYA MINANG - Choiru Pradhono (Institut Seni Budaya Indonesia Bandung, 2021)
Films are audio-visual media that are very effective in conveying information to the wider community in a distinctive way of telling. According to David Bordwell, film telling uses two main elements, namely form and style. Through a qualitative method with data collection techniques, observation, literature study and textual analysis of films with a Minangkabau cultural background which has its own way of conveying messages and information. In terms of phenomena, films are very effective as a medium for cultural diplomacy both to domestic and foreign audiences. So that the film is actually formed from the vision of the story and the ideas behind it and in its own way becomes a medium of communication.